Relationship between behavioral alterations and activities of adenylate kinase and creatine kinase in brain of rats infected by Trypanosoma evansi - Baldissera M.D. (2015)
© 2015 Elsevier Inc.The aim of this study was to investigate the behavioral assessment and activities of important enzymes involved in the phosphoryl transfer network in rat brains that were experimentally infected with Trypanosoma evansi. Behavioral assessment (cognitive performance), pro-inflammatory cytokines in serum and activities of adenylate kinase (AK), pyruvate kinase (PK), and creatine kinase (CK) in brain were evaluated at 5 and 15 days post-infection (PI). Here we demonstrate a cognitive impairment in the rats infected with T. evansi. At 5 and 15 days PI, a memory deficit and a depressant activity were demonstrated by an inhibition avoidance test and increase in the immobility time in a tail suspension test, respectively. On day 5 PI, a decrease in the CK activity and an increase in the AK activity were observed. On day 15 PI, an increase in the CK activity and a decrease in the AK activity were observed. Considering the importance of energy metabolism for brain functioning, it is possible that the changes in the activity of enzymes involved in the cerebral phosphotransfer network and an increase in the proinflammatory cytokines (TNF and IFN) may be involved at least in part in the cognitive impairment in infected rats with T. evansi.